Dynamic and thermal behaviour study of a complex network of gas pipeline in transient flow - Touabti, M.C.A. (2009)
Gas is the primary energy source of which the progression in the world energy demand is the most spectacular. The routing of gas to consumers is done through networks of pipelines.The hypothesis of stationary aspect in the conception of pipeline networks is bound mainly to the mathematical difficulties describing the non stationary out-flow in a complex network of pipelines: differential equation systems of non linear partial derivatives of very big dimension. The monumental progress of computing led to the apparition of very powerful dynamic simulators (SIMONE, TGNET) that can take into account pipeline networks including several thousands of nodes and all possible configurations in stationary and especially non stationary regime [5]. We suggest in this subject a modelling and simulation of a real pipeline with variable and transient regime and to study by means of numerical simulations the dynamic behaviour of gas in pipeline by means of several scenario.